Research on a new modular chain guided by vision - Xie, Ming. (2008)
The principal objective of this project is to investigate the interaction between vision and robotics. The key emphasis is placed on the exploration of robotics kinematics to improve the process of vision-guided control of robotics system such as head-eye coordination and hand-eye coordination.